2005
DOI: 10.1111/j.1365-2222.2006.02401.x
|View full text |Cite
|
Sign up to set email alerts
|

Levan (β‐2, 6‐fructan), a major fraction of fermented soybean mucilage, displays immunostimulating properties via Toll‐like receptor 4 signalling: induction of interleukin‐12 production and suppression of T‐helper type 2 response and immunoglobulin E production

Abstract: Levan is an immunostimulatory moiety in products from the fermentation process of B. subtilis (natto) and may be useful for prevention of allergic disorders with IgE production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…The mode of action behind the downregulation of elevated proinflammatory cytokine synthe- It was found that levan is one of the potential immunstimulant components released into the supernatant by B. amyloliquefaciens CECT 5940 equipped with levansucrase enzyme [53]. The immunstimulant activity of levan appears to rely on induction of Toll-like receptor 4 (TLR-4) signalling partially through induction of IL-12 production [54]. In our study, modulated response of proinflammatory cytokine network was achieved by applying only SCS of B. amyloliquefaciens alone expressed in upregulated IL-8 and TNF-α relative gene expression level in IPEC-J2 cells.…”
Section: Discussionmentioning
confidence: 98%
“…The mode of action behind the downregulation of elevated proinflammatory cytokine synthe- It was found that levan is one of the potential immunstimulant components released into the supernatant by B. amyloliquefaciens CECT 5940 equipped with levansucrase enzyme [53]. The immunstimulant activity of levan appears to rely on induction of Toll-like receptor 4 (TLR-4) signalling partially through induction of IL-12 production [54]. In our study, modulated response of proinflammatory cytokine network was achieved by applying only SCS of B. amyloliquefaciens alone expressed in upregulated IL-8 and TNF-α relative gene expression level in IPEC-J2 cells.…”
Section: Discussionmentioning
confidence: 98%
“…This is in agreement with Chen and Ainsworth [30], where no difference in leucocyte was observed in Channel catfish when injected with b-glucan. Studies carried out by Xu et al [31] have inferred that Toll like receptor 4 is involved in pattern recognition of levan.…”
Section: Discussionmentioning
confidence: 98%
“…It is an ideal soluble dietary fiber (Peshev and Van den Ende 2014) which is nondigestible and presents favorable prebiotic properties ). In addition, it exhibits antiobesity (Oh et al 2014), antioxidant (Dahech et al 2013), hypocholesterolemic (Yamamoto et al 1999), hypolipidemic , fibrinolytic (Esawy et al 2013), immunostimulatory (Xu et al 2006), and antitumor effects . Furthermore, levan is also a potential substitute for gum arabic due to its low viscosity and high water solubility (Han 1990).…”
Section: Levan Biosynthesismentioning
confidence: 99%